Stability and kinetic behavior of immobilized laccase from Myceliophthora thermophila in the presence of the ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate - María Férnandez-Férnandez (2014)
The use of ionic liquids (ILs) as reaction media for enzymatic reactions has increased their potential because they can improve enzyme activity and stability. Kinetic and stability properties of immobilized commercial laccase from Myceliophthora thermophila in the water-soluble IL 1-ethyl-3-methylimidazolium ethylsulfate ([emim][EtSO4]) have been studied and compared with free laccase. Laccase immobilization was carried out by covalent binding on glyoxyl-agarose beads. The immobilization yield was 100%, and the activity was totally recovered. The Michaelis-Menten model fitted well to the kinetic data of enzymatic oxidation of a model substrate in the presence of the IL [emim][EtSO4]. When concentration of the IL was augmented, the values of V-max for free and immobilized laccases showed an increase and slight decrease, respectively. The laccase-glyoxyl-agarose derivative improved the laccase stability in comparison with the free laccase regarding the enzymatic inactivation in [emim][EtSO4]. The stability of both free and immobilized laccase was slightly affected by small amounts of IL (<50%). A high concentration of the IL (75%) produced a large inactivation of free laccase. However, immobilization prevented deactivation beyond 50%. Free and immobilized laccase showed a first-order thermal inactivation profile between 55 and 70 degrees C in the presence of the IL [emim][EtSO4]. Finally, thermal stability was scarcely affected by the presence of the IL. (C) 2014 American Institute of Chemical Engineers